Ukuphumelela: Flourishing and the pursuit of a good life, and good health, in Soweto, South Africa - Lindile Cele; Sarah S. Willen; Maydha Dhanuka; Emily Mendenhall (Elsevier, 2021)
What does it mean to live a flourishing life in Soweto? This article investigates how people residing in Soweto, located in South Africa's Gauteng province, define, experience, and express flourishing both on its own and in relation to health. We interviewed 30 people who had expressed some interest in flourishing and health in a previous interview, and found that the IsiZulu term ukuphumelela - roughly translated as "becoming victorious" - best approximated the English notion of flourishing. We found that interviewees' conceptions of ukuphumelela diverged significantly from current scholarship on flourishing in general and flourishing and health in particular. Three central elements of ukuphumelela illustrate three elements: external, material, or structural factors (like financial security), internal or personal characteristics (including discipline), and relationality of social dynamics, such as dynamics of reciprocity, mutual obligation, and care. Moreover, we identified seven ways people drew from their personal journeys to define ukuphumelela: 1) determination and drive to reach their goals; 2) broader opportunity to attain a good education and learn from strong role models or mentors; 3) having enough money or material support to cover basic needs; 4) overcoming odds or conquering challenges from childhood; 5) prayer, faith, and trust in God; 6) a journey or path (a pursuit); and 7) caring for and giving back to others, emphasizing ubuntu. Our findings suggest that what it means, and what it takes, to flourish varies from one setting to the next.